Solar radiation absorption according to the tree crown conduction and the effects on peach cultivars production - Schneider, Evandro Pedro; Schöffel, Edgar Ricardo; Fachinello, José Carlos (Comunicata Scientiae, 2018)
In order to reach high productive efficiency, three training systems of the crown in peach trees were evaluated for the efficiency of absorption of solar radiation, aiming to identifying which system of conduction can provide a higher absorption of solar radiation and its effects on the production of the ‘Eldorado’ and ‘Jubileu’ peach cultivars. The crown of the trees were conducted in Central Leader, Y-shape and in open Vase systems. Measuring the global solar radiation, reflected solar radiation and the transmitted solar radiation, it was possible to obtain the absorbed solar radiation and the efficiency in radiation absorption by each system of conduction. The ‘Jubileu’ and ‘Eldorado’ peach trees were not different for the solar radiation absorption. The Central Leader and open Vase systems present capacity to retain up to 75% of the solar incident radiation while the Y-shape system retains up to 45% of the radiation. The peach production in the open Vase system resulted in 36.1 kg plant-1, higher than 25.47 kg plant-1 obtained in the Central Leader system, while the production in Y-shape system reached the production of 29.85 kg plant-1.